Downregulation of Dynamin-Related Protein 1 Contributes to Impaired Autophagic Flux and Angiogenic Function in Senescent Endothelial Cells. Issue 6 (June 2015) - Lin, Jing-Rong; Shen, Wei-Li; Yan, Chen; Gao, Ping-Jin
<x xml:space="preserve">Abstract</x> Objective— Recent studies have shown that altered mitochondrial dynamics impairs the function in senescent endothelial cells (ECs). However, the underlying molecular mechanism remains to be elucidated. Herein, we investigated the role and underlying mechanism of mitochondrial fission protein dynamin-related protein 1 (DRP1) in vascular aging. Approach and Results— We found that DRP1 expression is decreased in senescent ECs, accompanied with long interconnected mitochondria and impaired angiogenic function. In addition, there was marked increase of autophagosomes but not of autolysosomes (assessed as punctate dual fluorescent mCherry-GFP (green fluorescent protein) tandem-tagged light chain 3 expression) in senescent ECs, indicating impaired autophagic flux. DRP1 knockdown or pharmacological inhibition in young ECs resulted in elongated mitochondria, suppressed autophagic flux, premature senescence, and impaired angiogenic function. In contrast, adenoviral-mediated overexpression of DRP1 in senescent ECs restored autophagic flux and improved angiogenic function. EC senescence was associated with the increase of mitochondrial reactive oxygen species and antioxidant N-acetyl-cysteine restored autophagosome clearance and improved angiogenic function. Consistently, en face staining of old rat thoracic aorta revealed a decrease of DRP1 expression and increase of autophagosomes accumulation. Furthermore, in vivo knockdown of Drp1 in common carotid arteries significantly impaired the autophagosome clearance. Importantly, downregulation of Drp1 directly abrogated microvessels outgrowth from ex vivo aortic rings. Conclusions— These results suggest that loss of DRP1 during senescence exacerbates ECs dysfunction by increasing mitochondrial reactive oxygen species and subsequently inhibiting autophagic flux.